Efecto De Sobrealimentos A Base De Tres Mezclas Alimenticias (Industrial Y Natural), Sobre La Producción De Leche En Ganado Vacuno (Hostein) - Saavedra, Hilter Farley Figueroa (European Scientific Journal, ESJ, 2017)
The main objective of this research is to evaluate the effect of three types of superfoods based on three food mixtures (artificial and natural) in the milk production of cattle (Mestiza breed). In the study, there was a reduced milk production due to the difficulties in feeding cattle. Producers use the traditional grass of low nutritional value due to the impossibility of having high cost balances as a basic problem in this preliminary work. Milk production was increased by the use of food mixtures. These mixtures are composed of different percentages of natural pastures (Gliricidia sepium, Trichanthera gigantea, Pueraria phaseoloides and Saccharum officinarum) and artificial foods (mineralized salt and Palmister obtained from palm oil). The best results in milk production occurred in treatments 5 and 6 which significantly outperformed the rest. However, the highest profitability (utility) was reached in treatment 7.